Synergistic targeting of CHK1 and mTOR in MYC-driven tumors. (18th November 2020) - Song, Xiaoxue; Wang, Liyuan; Wang, Tianci; Hu, Juncheng; Wang, Jingchao; Tu, Rongfu; Su, Hexiu; Jiang, Jue; Qing, Guoliang; Liu, Hudan
Abstract: Deregulation of v-myc avian myelocytomatosis viral oncogene homolog (MYC) occurs in a broad range of human cancers and often predicts poor prognosis and resistance to therapy. However, directly targeting oncogenic MYC remains unsuccessful, and indirectly inhibiting MYC emerges as a promising approach. Checkpoint kinase 1 (CHK1) is a protein kinase that coordinates the G2/M cell cycle checkpoint and protects cancer cells from excessive replicative stress. Using c-MYC-mediated T-cell acute lymphoblastic leukemia (T-acute lymphoblastic leukemia) and N-MYC-driven neuroblastoma as model systems, we reveal that both c-MYC and N-MYC directly bind to the CHK1 locus and activate its transcription. CHIR-124, a selective CHK1 inhibitor, impairs cell viability and induces remarkable synergistic lethality with mTOR inhibitor rapamycin in MYC -overexpressing cells. Mechanistically, rapamycin inactivates carbamoyl-phosphate synthetase 2, aspartate transcarbamoylase, and dihydroorotase (CAD), the essential enzyme for the first three steps of de novo pyrimidine synthesis, and deteriorates CHIR-124-induced replicative stress. We further demonstrate that dual treatments impede T-acute lymphoblastic leukemia and neuroblastoma progression in vivo . These results suggest simultaneous targeting of CHK1 and mTOR as a novel and powerful co-treatment modality for MYC-mediated tumors. Abstract : Summary: Oncogenic c-MYC/N-MYC directly activates CHK1 to ameliorate replicative stress in cancer cells. As mTOR inhibition suppresses de novo pyrimidine synthesis and enhances replicative stress, pharmacological inhibition of CHK1 and mTOR induces remarkable synergistic lethality in MYC-overexpressing tumor cells.